Evaluating river driftwood as a feedstock for biochar production. (October 2021) - Qatarneh, Abdullah F.; Dupont, Capucine; Ruiz-Villanueva, Virginia; da Silva Perez, Denilson; Ashour, Radwa M.; Piégay, Hervé; Franca, Mário J.
Highlights: Globally more than 3 million tons of river driftwood are extracted annually. Driftwood transportations eliminate bark without degrading the macromolecules. Wood fraction of river driftwood has similar properties to fresh wood. River driftwood can be thermally processed without any prior separation. Abstract: Driftwood in river catchments might pose a hazard for the safety of infrastructures, such as dams and river dwellers, and thus is often removed. Génissiat dam in France presents a case study where annually approximately 1300 tons of driftwood are removed to prevent driftwood sinking and to protect the dam infrastructure. Collected river driftwood is rarely studied for utilization purposes and is commonly combusted or landfilled. However, driftwood can be valorized for biochar production through pyrolysis or hydrothermal carbonization (HTC). This study follows a novel approach in characterizing river driftwood by identifying the different common genera present at Génissiat dam on the upper Rhône, France. Moreover, the research provides for the first time a comprehensive analysis of river driftwood different physico-chemical properties, such as moisture content, major elemental composition (CHNSO), HHV, and macromolecular composition (cellulose, hemicellulose, lignin, and extractives). The study shows that the transportation of driftwood through rivers can enhance its properties by reducing the bark content resulting in lower ash content. Results indicate that driftwood can be mixed and further processed as a feedstock regardless of their genera and type for biochar production by pyrolysis or hydrothermal carbonization.